Robotic adrenalectomy for sigmoid colon cancer oligometastasis - Pai, Vishwas D. (Ann Transl Med, 2015)
Solitary adrenal metastasis from colorectal cancer is rare with reported incidence from 3.1% to 14.4% in the literature. Conventionally, adrenal metastasis is considered as indicative of widespread systemic disease and hence treated with palliative intent. Surgical resection remains controversial although a median survival of 32 months was found in the largest reported case series. It has been postulated that surgical resection should be offered when the adrenal metastasis develops more than 6 months after the treatment of the primary tumor. For the metastatic lesions and potentially malignant lesions, role of minimally invasive surgery is still considered controversial. We are presenting a case of metachronous, solitary adrenal metastasis from sigmoid colon carcinoma treated surgically with curative intent.